Economic integration and FDI: an empirical analysis of foreign investment in the EU and in Central and Eastern Europe - Paul Brenton; Francesca DiMauro; Matthias Lücke (ACE Programme Management; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2001)
Recent evidence suggests that regional economic integration provides an important stimulus not only to trade, but also to FDI. In contrast, the available theory on FDI does not yet provide empirically testable propositions on the effects of concurrent trade and investment liberalisation. Moreover, given the limits of simulation models, which rely heavily upon parameter choice, in assessing the impact of such liberalisation, there is a need for empirical analysis to identify the principal features of FDI. This paper uses a 'gravity model' approach to assess the impact of the deepening integration between the EU and the CEECs on FDI flows in terms of three key issues. First, we provide systematic estimates of the expected long-term level of FDI in the CEECs. Second, we investigate whether FDI in the CEECs, on the one hand, and source country exports and imports, on the other hand, are complements or substitutes. Finally, we enquire whether an increase in the attractiveness of the CEECs to foreign investors has affected the magnitude of FDI going to other European countries.
Keywords: F15; F21; F23; 330; Direktinvestition; Gravitationsmodell; EU-Erweiterung; Internationale Wirtschaftsbeziehungen; Wirtschaftsintegration; Schätzung; EU-Staaten; Osteuropa